2016
DOI: 10.1002/ange.201608792
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox Activation of SF6 for Fluorination

Abstract: We report the first practical use of SF6 as a fluorinating reagent in organic synthesis. Photoredox catalysis enables the in situ conversion of SF6, an inert gas, into an active fluorinating species by using visible light. Under these conditions, deoxyfluorination of allylic alcohols is effected with high chemoselectivity and is tolerant of a wide range of functional groups. Application of the methodology in a continuous‐flow setup achieves comparable yields to those obtained with a batch setup, while providin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In another approach to incorporate fluorine into organic molecules using continuous photoredox catalysis, McTeague et al reported the use of gaseous SF 6 for deoxyfluorinations of allylic alcohols (Scheme 155). 716 The reaction system was Prior to irradiation, a small residence time unit was installed for better mixing. Further, a system pressure of 6.9 bar was utilized to increase the solubility of the gaseous fluorine source.…”
Section: •−mentioning
confidence: 99%
“…In another approach to incorporate fluorine into organic molecules using continuous photoredox catalysis, McTeague et al reported the use of gaseous SF 6 for deoxyfluorinations of allylic alcohols (Scheme 155). 716 The reaction system was Prior to irradiation, a small residence time unit was installed for better mixing. Further, a system pressure of 6.9 bar was utilized to increase the solubility of the gaseous fluorine source.…”
Section: •−mentioning
confidence: 99%
“…Similar photo-initiated deoxyfluorination reactions involving SF 6 and a range of molecules have been observed in solution, although the mechanistic details are somewhat obscure. [38][39][40][41] We investigated the formation of the photoproduct from NPOO − as a function of the SF 6 partial pressure, which is conveniently assessed from the arrival time of the NPOO − peak; following Blanc's law, 42 the increase in the arrival time should be proportional to the SF 6 partial pressure. The relative yields of the photoproduct and SF -6 are plotted in Fig.…”
Section: Photodetachment and Photochemistry Of 6-hydroxy-2-mentioning
confidence: 99%
“…SF 6 is described in the literature as a highly stable, nonreactive gas, [39][40] and therefore, relatively little remained known about its room-temperature reaction chemistry until fairly recently. [41][42][43][44][45] Owing to its octahedrally-coordinated shell of highly electronegative fluoride ligands, SF 6 is nonpolar, and exhibits high dielectric strength and electron-capture ability that make it a good dielectric insulator. Its spark breakdown under high electric fields, and subsequent gas-phase decomposition products, have been studied in this context, 46 and help to inform our own analysis in considering accessible electrochemical reduction pathways.…”
Section: Resultsmentioning
confidence: 99%